A facile approach for grafting bi-functional groups terminated branched polyphosphazene on carbon fibers - Z. J. He; J. H. Liu; S. H. Liu; X. Q. Zhang; C. H. Lei (eXPRESS Polymer Letters, 2020)
We explored a facile method for grafting bi-functional groups terminated branched polyphosphazene on carbon fibers via direct epoxy amination with an aqueous ammonia solution. The branched polyphosphazene with abundant β-hydroxyl groups and amino groups significantly changes the chemical composition of carbon fibers surface. A significant improvement in interfacial shear strength was obtained from 43.6 MPa for virgin carbon fibers (C.F.) composites to 89.6 MPa for branched polyphosphazene grafted C.F. composites.